THE CONTRIBUTIONS OF CELL BIOLOGY STUDIES TO THE FIELD OF AESTHETICS, HEALTH AND LASER THERAPY - Gomes Do Valle, Lívia (Health and Society, 2023)
This article seeks to evaluate the contributions of Cell Biology studies to the field of Aesthetics, Health and also laser therapy. It is, in fact, about relating these four areas through a systematic literature review. This review took place on a data platform and considered scientific productions (including theses, dissertations and articles) produced in the last five years that articulated these three subjects. After establishing the descriptors, inclusion and exclusion criteria, the returned searches were submitted to the latter, reaching the number of 06 studies that were evaluated according to the perspective of the contribution of studies and research in Cellular Biology to the technological advances of laser therapy for aesthetic purposes. Although the aesthetic purpose was something pre-established and of great importance for this research, other benefits of laser therapy directly linked to health were noted. As a result, it was concluded that the studies evaluated point to the importance of investments in the area of Cellular Biology as a way of developing new approaches, applications or recommendations for the use of laser therapy for aesthetic purposes.